Posted by **John** on Tuesday, April 29, 2008 at 10:30pm.

f(x)=5+(6/x)+(7/x^2), find f'(x).

I haven't done fractions without using the quotient rule im not so sure this would work with quotient rule what do i do?

- Calculus -
**Quidditch**, Tuesday, April 29, 2008 at 11:13pm
rewrite as:

f(x)=5 + 6*x^(-1) + 7*x^(-2)

The derivative of the first term is 0. For the derivative of the terms with x, multiply the exponent times the coeffecient of the term, the subtract 1 from the exponent.

## Answer this Question

## Related Questions

- Calculus - Let f(x)= 5x ------- x–2 are we supposed to use the quotient rule? ...
- Calculus - How do I use the chain rule to find the derivative of square root(1-x...
- Calculus - Match the rule with the title: ____ 3. d/dx [f(x)/g(x) ]=(g(x) f^' (x...
- Calculus - y= [(x-3)/(x^2+1)]^2 find the derivative. I know i would start off ...
- Calculus-Math - Complete the table without using the Quotient Rule. Function y=...
- Calculus - y= [(x-3)/(x^2+1)]^2 I know that I would use the product rule on the ...
- calculus - Please help. Applying the chain rule, how do I find the derivative of...
- Calculus - Find the derivative of y=x^2 / e^2x using the Quotient Rule, and ...
- Calculus - Find f''(1/2) using f(x) = ln(1-x). f'(x) = 1/(1-x) * -1 = -1/(1-x) ...
- Calculus - What would an example of a logarithmic function that contains a ...